SELF CARE DAN KUALITAS HIDUP PADA PASIEN DIABETES MELITUS - Sarmaida Siregar; Ratna Dewi; Baharudin Yusuf Munthe (Jurnal Ilmiah Keperawatan IMELDA, 2022)
Diabetes Mellitus is a health disorder caused by increased blood sugar levels due to insulin deficiency or resistance. This disease has long been known, especially among large families (overweight) along with a high lifestyle. This study was conducted to determine the relationship between self care and the quality of life of diabetes mellitus patients at the Imelda general hospital for Indonesian workers in Medan in 2021. The sample in this study was 30 respondents. This study was taken based on univariate and bivariate data through the chi-square test. The results showed that self care was related to the quality of life of patients with diabetes mellitus (Ket: P < 0.00). It is recommended for people with diabetes mellitus to maintain their diet, activity, routinely check blood sugar levels according to the advice of health and self-care professionals in order to improve their quality of life.